“Impact of Emotional Intelligence on Managerial Effectiveness” (A Case Study) - Vyas, Priyanka; Yadav, Ravindra; Sharma, Jyoti (International Journal of Computer Sciences and Engineering, 2025)
With the advent of the 21st century, the role of emotional intelligence is important to provide their services in the perspective of managerial effectiveness. In this study, the researcher has attempted to examine the impact of emotional intelligence on managerial effectiveness in Employees State Insurance Corporation.. This sector is very vital to protect the employees and very much conscious about their social security. An amplified reliance on computerized technology, teleworking, self-regulated work and team work; all these changes move towards a more flexible and elastic personnel management, both in number of increasing human power and in their skills and competencies. The adjustments with the changing conditions of work and employment are responded by significantly. With the growth of information technology, leaner & flexible processes have increased the demand for competent managers for handling the multi – task. For this study total 400 employees of Employees State Insurance Corporation were selected to examine the impact of emotional intelligence on managerial effectiveness.